A chemical process engineering look at digital concrete processes: critical step design, inline mixing, and scaleup - Wangler, Timothy; Pileggi, Rafael; Gürel, Seyma; Flatt, Robert J. (Cement and concrete research, 2022)
Digital concrete processes are a series of unit operations, similar to a chemical engineering process, each subject to their own rheological and other performance requirements, such as homogeneity, etc. In this article we examine the concrete extrusion 3D-printing process from this standpoint, first decomposing it into individual unit operations. We examine the role that residence time distributions play in the overall process, and then analyze how large scale printing to structural heights could be performed continuously. We then focus on the critical step of secondary (inline) mixing just before extrusion from the standpoint of mixing processes in the chemical processing industries. This unit operation is then analyzed in the context of scaleup to larger print areas and larger flowrates, finding that increase in viscosity plays a major role in power requirements and printhead mass. Further research questions are then raised based on these analyses.